PhoVoSS Java implementation of a circuit simulator with photovoltaic system modeling capability - Ureta, Orlando Jr. H.
We developed a simulation program front-end electronic circuits as well as photovoltaic systems. This simulation program was written in Java and has a graphical user interface (GUI) for the convenience of the user. It has schematic capture to get the schematics from the user. It uses XSPICE as its backend simulator and graphs the simulation results using a waveform viewer. The program can be used in Windows and Linux. Finally, the simulator can be extended by adding or modeling user-defined components.